Test of Antidiabetic Effect of Taro Leaf Extract (Colocasia esculenta L.) on Zebrafish (Danio rerio) - Adelia Nurrochifah; Hendra Stevani; Ratnasari Dewi (Journal of Tropical Pharmacy and Chemistry, 2023)
Diabetes mellitus (DM) is a common metabolic disorder defined as chronic hyperglycemia. In addition to the symptoms associated with hyperglycemia itself such as thirst, polyuria and weight loss, it can also cause acute hyperglycemia emergencies that are potentially life threatening. One of the traditional plants that has potential as an antidiabetic drug is the taro plant (Colocasia esculenta L) because it contains chemical compounds such as alkaloids, flavonoids, saponins, tannins and polyphenols which are known to have antidiabetic effects. This study aims to determine the effectiveness and what dose of Taro Leaf Extract gives the best effect of reducing blood glucose levels in zebrafish. This study used zebrafish (Danio rerio) induced with alloxan and glucose to raise blood glucose levels. The 20 test animals used were divided into 6 groups, namely group 1 without treatment (normal), group 2 control (-) alloxan induction 0.1% + glucose 1%, group 3 control (+) metformin, group 4 taro leaf extract 200 mg, group 5 taro leaf extract 300 mg, group 6 taro leaf extract 400 mg. Then glucose levels were measured using a glucometer. Data analysis was carried out statistical tests. The results showed that a dose of 400 mg/2L had the ability to reduce blood glucose levels that were not significantly different from normal zebrafish glucose levels.